2012
DOI: 10.1007/s10750-012-1028-x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of escaped farmed rainbow trout (Oncorhynchus mykiss) as a vector for the salmon louse (Lepeophtheirus salmonis) depends on the hydrological conditions in the fjord

Abstract: The objectives of the study were to see if escaped rainbow trout (Oncorhynchus mykiss) spread rapidly or not from fish farms, and to test whether the hydrological conditions in a fjord influence their vertical distribution and importance as vector for the salmon lice (Lepeophtheirus salmonis). Fifty farmed rainbow trout were tagged with acoustic transmitters including depth sensors and released from two of 11 fish farms in the fjord system. In addition, unintentionally escaped rainbow trout were recaptured for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
3
27
1
Order By: Relevance
“…the exotic rainbow trout (both farm escapees and wild) and the native P. trucha, the former dominating at shallow depths and the latter at greater depths. Escaped (ERT) and wild (WRT) rainbow trout each accounted for c. one third of the total littoral capture (<4 m), coinciding with other studies on depth distribution of farm escapees (Chittenden et al, 2011;Skilbrei, 2012;Patterson and Blanchfield, 2013). Diet differences between species were marked, paralleling the observed segregation by depth.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…the exotic rainbow trout (both farm escapees and wild) and the native P. trucha, the former dominating at shallow depths and the latter at greater depths. Escaped (ERT) and wild (WRT) rainbow trout each accounted for c. one third of the total littoral capture (<4 m), coinciding with other studies on depth distribution of farm escapees (Chittenden et al, 2011;Skilbrei, 2012;Patterson and Blanchfield, 2013). Diet differences between species were marked, paralleling the observed segregation by depth.…”
Section: Discussionsupporting
confidence: 84%
“…Two studies in Norwegian sea fjords reported numerous indigestible items in ERT stomach contents with less than a year in the wild, but not farm pellets or wild food (Rikardsen and Sandring, 2006;Skilbrei, 2012). Wild food and farm pellets, but not indigestible items, were found in ERT with probably more than a year since escape time in Chilean sea fjords (Soto et al, 2001) and lakes (Arismendi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations